Factors influencing auditor selection in Malaysian Listed Companies / Mohd Shaharuddin Masri - Masri, Mohd Shaharuddin (2015)
This research investigates whether the company's characteristics, such as size of audit committee, audit committee independence, audit report lag and audit fee are associated with the auditor selection. The sample of this study covers all companies which have been listed in main and second board at Bursa Malaysia. This study use 648 sample population of public listed company after considering the incomplete data from the 2014 annual report such as missing data of audit firm, audit committee size, audit report lag, audit fee, non-audit service and growth of the company. Using the logistic regression analysis, the findings show that there is significant relationship between company's characteristics (audit report lag and audit fee) and auditor selection and the other variables do not support the hypotheses of this study. Specifically, the result shows that auditor selection is negatively associated with audit report lag. This result shows that company's decision will select a Big-4 audit firm that usually has lesser audit delay. Audit fee shows significant result suggesting audit fee has a significant relation with auditor selection. In addition, clients are willing to pay higher audit fees for a better audit quality, thus decide to choose a Big-4 audit firm to perform a better quality audit for the company. Overall, this research contributes new evidence on the factors that explain the making decision on auditor selection.